FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Periode 2009 â 2012) - Ryan Aldo Saputra, 09.05.52.0053 (Students Journal of Accounting and Banking, 2013)
This study aims to analyze whether the size of the profit or loss, the auditors opinion, profitability, firm size, the reputation of public accounting firms, and the effect on the solvency of the companys audit report lag in companies listed on the Indonesia Stock Exchange.The population is a manufacturing company listed on the Stock Exchange in 2009 - 2012. The samples in this study were 180 companies (4 years). The sampling method using purposive sampling method. While the method of data analysis using descriptive statistics and multiple regression analysis. To meet the regression model used to represent the classical assumption.Results of this study show a profit or loss, profitability, firm size, the size of public accounting firms, and solvency, had significant influence in reducing the audit report lag. While the auditors opinion does not have a significant effect in reducing the audit report lag.Keywords: Audit Report Lag, profit or loss, auditors opinion, profitability, firm size, the size of public accounting firms, and solvency